PSYCHOLOGICAL BARRIERS ON EFL STUDENTS’ SPEAKING PERFORMANCE IN BORDER AREA - Wisrance, Maria Wihelmina; Kristanti, E (Universitas Muhammadiyah Makassar, 2024)
Oral communication has emerged as a crucial skill in language acquisition, particularly in learning English. For students learning English as a foreign language, speaking English poses a significant challenge that requires considerable effort to articulate coherent statements. The research focused on identifying psychological factors that impact students' speaking performance, with a particular emphasis on determining which variable has the most significant effect. Data was gathered through observation, questionnaires, and unstructured interviews. The study revealed that despite students' motivation and positive attitude towards English speaking in the classroom, anxiety and lack of self-confidence remain key obstacles that prevent them from speaking confidently. These psychological barriers stem from a fear of erring and being subjected to derision by one's peers. Further, it was found that anxiety was the most psychological factor affecting students’ speaking performance. To address these issues, many students believe that boosting their confidence in speaking English is crucial. This underscores the significance of educators being mindful of the difficulties their students face in speaking English during lessons.